Digital Promotion And Financial Literacy In Food Stall Traders Group In Mautapaga District: Promosi Digital Dan Literasi Keuangan Pada Kelompok Pedagang Warung Makan Di Kelurahan Mautapaga - Yulius Laga; Gabriel Tanusi (Institut Riset dan Publikasi Indonesia, 2023)
This service activity was carried out as a form of participation to the community in the face of the Covid 19 pandemic, specifically for merchant groups in the Mautapaga Village area, Ende Regency, East Nusa Tenggara (NTT) Province. The service was carried out for 2 days starting from 6 to 7 November 2020. This community service was carried out with the lecture method by providing material as well as practice in making simple promotions digitally (online) by utilizing social media besides that the merchant group was also given an understanding of financial management in simple terms (Financial Literacy) to manage business finances. This activity involves 5 groups of traders and 10 students, the results of this activity are expected to contribute to understanding for the community of merchant groups in an effort to increase business promotion and gain a general understanding of financial literacy, another output is field practice for students who have taken entrepreneurship courses.